Réponses

  • Utilisateur Brainly
2013-05-14T09:41:44+02:00

soit E(x)=(4x-7)²-(3+5x)(4x-7)

 

1) développement :

E(x)=16x²-56x+49-(12x+20x²-21-35x)

      =16x²-56x+49-20x²+23x+21

      =-4x²-33x+70

 

2) factorisation:

E(x)=(4x-7)(4x-7-3-5x)

      =(4x-7)(-x-10)

 

3) équations & inéquations :

a) E(x)=0

donc (4x-7)(-x-10)=0

donc 4x-7=0 ou -x-10=0

donc x=7/4 ou x=-10

 

b) E(x)>0

donc (4x-7)(-x-10)>0

obn effectue un tableau de signes

donc -10<x<7/4

 

c) E(x)=70

donc -4x²-33x+70=70

donc -4x²-33x=0

donc (-x)(4x+33)=0

donc -x=0 ou 4x+33=0

donc x=0 ou x=-33/4